Penerapan SAK EMKM dan Pengendalian Internal terhadap Kualitas Laporan Keuangan UMKM di Jombang - Adawiya Zahrotun Nisa; Dwi Ermayanti Susilo (Owner : Riset dan Jurnal Akuntansi, 2025)
Reliable financial reporting plays a crucial role in ensuring the long-term viability of Micro, Small, and Medium Enterprises (MSMEs). This research seeks to investigate the influence of implementing the Financial Accounting Standards for MSMEs (SAK EMKM) and internal control mechanisms on the quality of financial statements among MSMEs located in Jombang. A quantitative research design was employed, with data obtained through questionnaires distributed to 115 MSMEs, selected through purposive sampling from a total population of 500 businesses registered with the Jombang Cooperative Office. The sampling criteria required that MSMEs apply SAK EMKM and possess assets valued at a minimum of IDR 20,000,000, excluding land and buildings. Findings from the multiple regression analysis indicate that the implementation of SAK EMKM and the presence of internal control systems both have a significant impact on the quality of financial reporting. Specifically, the application of SAK EMKM has a positive effect, while internal control systems show a stronger impact. In conclusion, enhancing MSMEs’ understanding and consistent application of SAK EMKM, along with strengthening internal controls, are key strategies to improve financial reporting quality.